Early use of implantable loop recorders in the assessment of patients presenting to a district general hospital with syncope or severe palpitations with presyncope. (22nd September 2015) - Bajpai, A; Yavari, A; Asrress, KN; Cotterill, D; Dickinson, K; McWilliams, ET; Walker, DM
Abstract : Introduction: The use of implantable loop recorders (ILR) in patients with syncope is well established, but they are often reserved for patients who have undergone extensive previous investigations, including multiple ambulatory ECG recordings, patient activated devices, tilt-testing, and electrophysiological studies (EPS). In a district hospital setting tilt-testing and EPS are often less readily available. We decided to use ILR earlier in the algorithm and extended their use to patients with severe but infrequent palpitations with presyncope. Methods: We retrospectively analysed indications, time to diagnosis, diagnostic yield and therapeutic decisions in patients who received ILR between March 2004 and May 2008. Results: A total of 83 patients received an ILR during this period. Follow-up data of ⩾6 months was available in all patients. Mean age was 65 ± 20 years (range 17–93; 50% male). Indications for ILR were syncope (81%), severe presyncope (5%) and palpitations with presyncope (15%). All patients had previous 24-h ECG and/or a patient-activated device. A previous tilt test was performed in 32%. Symptom–ECG correlation was established in 54% of patients, whereas no dysrhythmias were detected in the remaining 46%. Among those with symptom–ECG correlation, the diagnosis was asystole greater than 3 s in 35%, high grade atrioventricular block in 7%, bradycardia (<30 bpm) in 7%, ventricular tachycardia in 9%, paroxysmal atrial fibrillation in 11%, and supraventricular tachycardia in 27%. In 13% a non-cardiac cause was confirmed. The mean time delay from first clinic review to ILR implantation was 182 ± 35 days. This delay was significantly longer in those who underwent tilt-testing (32%) or EPS (3%) before ILR implantation (n  =  20, 484 ± 104 days) versus those who received an ILR early after initial clinic review (n  =  70, 81 ± 20 days; p = 0.001). The mean duration from ILR implantation to specific diagnosis was similar in both groups (183 ± 78 days vs 172 ± 22 days, respectively; p = 0.6). This is clinically relevant as tilt-testing was non-contributory in the vast majority of cases, with only 2% revealing a cardioinhibitory and 6% a vasodepressor response. 46% of patients with symptom–ECG correlation subsequently underwent permanent pacemaker implantation, 8% had implantable cardioverter defibrillators, 21% received radiofrequency ablation and the remaining 25% were managed medically. The device was explanted in 84%. Average implant duration was 224 ± 28 days in patients with a positive diagnosis versus 667 ± 92 days in those with no symptom–ECG correlation (p = 0.001). Two devices were explanted early, one due to infection and one at the patient's request due to discomfort. Conclusion: Our data show a high diagnostic yield from the early use of ILR in this cohort. Early use of an ILR is likely to be cost effective in a district general hospital setting by reducing the number of unnecessary low-yield investigations and the time delay to specific therapeutic intervention.